DISEASES OF THE NERVOUS SYSTEM. - Amonova Zakhro Kakhramonovna,; Akmaljon Akhmatjonovich Gaybiyev,; Amonova Zilola Kahramonovna, (TADQIQOTLAR.UZ, 2024)
Abstract: In this article, we explore the fascinating and complex world of nervous system disorders, exploring the causes, symptoms, diagnosis, and treatment of the most common neurological disorders. By shedding light on these conditions, we aim to raise awareness, promote early detection, and improve the quality of care for individuals with neurological disorders.